Respuesta :

Answer:

(a+b)(a-b)

Step-by-step explanation:

[tex]\\ \sf\longmapsto (a+b)(a-b)[/tex]

[tex]\\ \sf\longmapsto a(a-b)+b(a-b)[/tex]

[tex]\\ \sf\longmapsto a^2-ab+ba-b^2[/tex]

[tex]\\ \sf\longmapsto a^2-ab+ab-b^2[/tex]

[tex]\\ \sf\longmapsto a^2-b^2[/tex]

According to the question

[tex]\large\bf{\orange{ \implies}} \: \tt \: {a}^{2} \: - \: {b}^{2} [/tex]

[tex]\large\bf{\pink{ \implies}} \: \tt \: (a + b) \quad \: (a - b)[/tex]

[tex]\large\bf{\pink{ \implies}} \: \tt \: a \: (a - b) \quad \: b \: (a - b)[/tex]

[tex]\large\bf{\pink{ \implies}} \: \tt \: {a}^{2} \: - \: ab \: + \: ba \: - \: {b}^{2} [/tex]

[tex]\large\bf{\pink{ \implies}} \: \tt \: {a}^{2} \: - \: ab \: + \: ab \: - \: {b}^{2} [/tex]

[tex]\large\bf{\pink{ \implies}} \: \tt \: {a}^{2} \: - \: \cancel{ab} \: + \: \cancel{ab} \: - \: {b}^{2} [/tex]

[tex]\large\bf{\pink{ \implies}} \: \tt \: {a}^{2} \: - \: {b}^{2} [/tex]